An epistemological critique of social entrepreneurship definitions - Amir Forouharfar; Seyed Aligholi Rowshan; Habibollah Salarzehi (Journal of Global Entrepreneurship Research, 2018)
If entrepreneurship is amid jungle of theories and has many theorists, its social orientation or what is known as social entrepreneurship (SE) is amid arid land of theories and suffers under-theorizing which could be inherently stemmed from its diversely proposed definitions. To be situated in an embryonic pre-paradigmatic phase, getting to a more unanimous definition in this realm is the first step in laying a solid foundation for SE theorizing. As a pioneering study, the paper aims to investigate the epistemological foundations of SE definitions critically to propose a more convergent definition for SE. To fulfill this goal epistemological justifications for the definitional components of SE are presented. Therefore, it was necessary to rely on the relevant philosophical schools of thought in Epistemology (e.g. Empiricism, Internalism, Externalism, Verificationism and Falsificationism); first to discuss the controversies and oppositions to some components of the definitions for their exclusion and then to justify some other definitional components which are mostly accepted by the scholars for their inclusion in a final SE definition. Critical approach has helped us in specifying the maneuvering of thoughts in this field and determining the epistemological and definitional boundaries of SE. Finally, a more epistemologically-supported and justified definition was presented at the end of the paper. Moreover, one of the potential contributions of this paper could be its consensus-making impact among SE scholars in defining SE phenomenon, which could also pave the way for future theorizing in SE. The originality of the paper lies in the application of Internalism, Externalism, Verificationism and Falsificationism concepts to SE definitions.
Keywords: 650; Social entrepreneurship (SE); Epistemology; Knowledge; Definition; Justification